Diagnostic performance of 99mTc-HYNIC-PSMA SPECT/CT for biochemically recurrent prostate cancer after radical prostatectomy - Li, Bo; Duan, Lili; Shi, Jingqi; Han, Yunyun; Wei, Wei; Cheng, Xiaoliang; Cao, Yong; Kader, Akeban; Ding, Degang; Wu, Xinyu; Gao, Yongju (Frontiers in Oncology, 2022)
Objectives: 99mTc-HYNIC-PSMA is a novel technetium-99m-labeled small-molecule inhibitor of prostate-specific membrane antigen (PSMA) for detection of prostate cancer. The present study investigated the diagnostic yield of 99mTc-HYNIC-PSMA Single photon emission computed tomography (SPECT)/CT in 147 patients with biochemically recurrent prostate cancer after radical prostatectomy. Methods: 147 patients with biochemical relapse after radical prostatectomy were finally eligible for this retrospective analysis. The median prostate-specific antigen (PSA) level was 8.26 ng/mL (range, 0.22-187.40 ng/mL). Of the 147 patients, 72 patients received androgen deprivation therapy (ADT) at least 6 months before the 99mTc-HYNIC-PSMA SPECT/CT. All patients underwent planar whole-body scans and subsequent SPECT/CT of the thoracic and abdominal regions after intravenous injection of 705±70 MBq of 99mTc-HYNIC-PSMA. Images were evaluated for the presence and location of PSMA-positive lesions, in which SUVmax were also measured. Detection rates were stratified according to PSA levels, ADT and Gleason scores. The relationships between SUVmax and clinical characteristics were analyzed using univariate and multivariable linear regression models for patients with positive findings. Results: Of the 147 patients, 99mTc-HYNIC-PSMA SPECT/CT revealed at least one positive lesion in 118 patients with a high detection rate (80.3%). The detection rates were 48.6% (17/35), 85.1% (40/47), 92.1% (35/38), and 96.3% (26/27) at PSA levels of greater than 0.2 to 2, greater than 2 to 5, greater than 5 to 10, and greater than 10 ng/mL, respectively. PSMA SPECT/CT indicated local recurrence, lymph node metastases, bone metastases, and visceral metastases in 14 (9.5%), 73 (49.7%), 48 (32.7%) and 3 (2.0%) patients. The detection rates of local recurrence and metastasis increased with increasing PSA levels. The detection rate was higher in patients treated with ADT than those without (90.3% vs. 70.7%; P =0.0029). In patients with Gleason scores ≥8, detection rate was slightly higher than those with ≤7 (81.7% vs. 78.5%), but not statistically significant (P = 0.6265). Multivariable linear regression analysis showed a significant correlation of PSA levels and ADT with SUVmax (P=0.0005 and P=0.0397). Conclusions: 99mTc-HYNIC-PSMA SPECT/CT offers high detection rates for biochemically recurrent prostate cancer after radical prostatectomy. The detection rate and SUVmax were positively correlated with PSA levels and ADT.